Perceived marginalization and mental health of young adults with migration backgrounds in South Korea: exploring moderating and mediating mechanisms - Jang, Sojung; Ryu, Jiwon; Yon, Kyu Jin; Kim, Paul Youngbin; Kim, Min Sun (Frontiers in Psychology, 2023)
This study explored the mediating effect of career maturity moderated by intimacy with parents and immigration backgrounds (native-or foreign-born young adults) on the relationship between perceived marginalization and the mental health of young adults with migration backgrounds (having mixed parentage of one Korean and one non-Korean immigrant parent) in South Korea. We collected data from 300 adults aged 25-34 with migration backgrounds (204 born in Korea and 96 born abroad) through the Gallup Research Institute of Korea and conducted a moderatedmoderated mediation analysis using Model 21 of PROCESS Macro in SPSS. The analysis showed that career maturity moderated by intimacy with parents and migration backgrounds mediated the relationship between perceived marginalization and mental health. However, the results were only significant for participants who were born abroad and immigrated to Korea, and not for those who were born in Korea. These findings suggest that while greater perceived marginalization leads to lower career maturity and negatively impacts the mental health of foreign-born young adults, higher levels of intimacy with parents can buffer these negative effects.